Choline Kinase Alpha2 Promotes Lipid Droplet Lipolysis in Non-Small-Cell Lung Carcinoma - Zhu, Rongxuan; Yang, Yannan; Shao, Fei; Wang, Juhong; Gao, Yibo; He, Jie; Lu, Zhimin (Frontiers in Oncology, 2022)
Background: Rapid tumor growth inevitably results in energy stress, including deficiency of glutamine, a critical amino acid for tumor cell proliferation. However, whether glutamine deficiency allows tumor cells to use lipid droplets as an energy resource and the mechanism underlying this potential regulation remain unclear. Methods: We purified lipid droplets from H322 and H358 human non-small-cell lung cancer (NSCLC) cells under glutamine deprivation conditions and performed immunoblotting to determine the binding of choline kinase (CHK)α2 to lipid droplets. Immunofluorescence was used to quantify lipid droplet numbers and sizes. Immunoprecipitation and immunoblotting were performed to examine AMPK activation and CHKα2 phosphorylation. Cellular fatty acid levels, mitochondrial acetyl coenzyme A and ATP production, and cell apoptosis and proliferation were measured. Immunohistochemical analyses were performed to determine the expression levels of ACC pS79 and CHKα2 pS279 in tumor specimens from NSCLC patients. The prognostic value of ACC pS79 and CHKα2 pS279 was assessed using the Kaplan-Meier method and Cox regression models. Results: Glutamine deficiency induces AMPK-mediated CHKα2 S279 phosphorylation, which promotes the binding of CHKα2 to lipid droplets, resulting in recruitment of cytosolic lipase ATGL and autophagosomes and subsequent lipolysis of lipid droplets to sustain tumor cell survival and proliferation. In addition, the levels of ACC pS79 and CHKα S279 were much higher in human NSCLC specimens than in their adjacent normal tissues and positively correlated with each other. Notably, ACC pS79 and CHKα pS279 expression levels alone were associated with poor prognosis of NSCLC patients, and combined values of both phosphorylation levels exhibited a better prognostic effect. Conclusion: CHKα2 plays a critical role in lipolysis of lipid droplets in NSCLC. ACC pS79 and CHKα2 pS279 alone or in combination can be used as prognostic markers in NSCLC.